Respuesta :

ANSWER

[tex]y = - 1+ 2 \sin(2x - 1)[/tex]

EXPLANATION

The given equation is

[tex]y = 1 + 2 \sin(2x - 1)[/tex]

This function is of the form,

[tex]y = a \sin(bx - c) + d[/tex]

The value of d=1 shifts the graph up by one unit.

If we want to shift the graph, 2 units down, then, we have to add -2 to d=1.

The transformed equation is,

[tex]y = - 2 + 1 + 2 \sin(2x - 1)[/tex]

which gives us,

[tex]y = - 1+ 2 \sin(2x - 1)[/tex]

Answer:

The equation will be y = -1 + 2 sin ( 2x - 1 )

Step-by-step explanation:

See the attached image

Ver imagen zainebamir540